Antihepatotoxic potential of Citrullus colocynthis root extract, fractions and isolated compounds - Mukerjee, Alok; Mishra, Shanti Bhushan; Saraf, Shubhini (Journal of Experimental Sciences, 2013)
Natural remedies from medicinal plants are considered to be effective and safe alternative treatment for liver toxicity. The article reveals the hepatoprotective activity of the ethanolic extract of the roots of the Citrullus colocynthis in rats using carbon tetrachloride (CCl4) model. On further fractionation of the ethanolic extract into three fractions, the activity was localized in the toluene fraction. These on purification led to the isolation of 2 pure compounds – Cucurbitacin B [1] and Colocynthin [2]. These two compounds showed promising activity in CCl4 model at 50 mg/kg dose level.